Urinary Tract Lithotripsy Using Holmium: YAG (2100nm) Laser - Khudhair, Qabel S.; Mahmood, Ali S.; Mahdi, Haider (Iraqi Journal of Laser, 2020)
Background: Laser urinary stone lithotripsy is an established endourological modality. Ho:YAG(2100nm) laser have broadened the indications for ureteroscopic stone managements to include larger stone sizes throughout the whole urinary tract. Purpose: To evaluate the effectiveness and safety of Holmium: YAG(2100nm) laser lithotripsy with a semirigid uretero scope for urinary stone calculi in a prospective cohort of 17 patients. Patients and Methods: Holmium: YAG(2100nm) laser lithotripsy was performed with a semirigid ureteroscope in 17 patients from September 2016 to December 2016. Calculi were located in the lower ureter in 9 patients (52.9%), the midureter in 5 (29.4%), and the upper ureter in 3 (17.64%).The parameters used were, average Power(20W),Energy(1.5-2J),Pulse duration(75-100ms),Frequency(10Hz) and Spot size(0.55mm). Results: The overall stone-free rate was (100%), this rate being for calculi in the lower ureter ,midureter and for calculi in the upper ureter. Complications occurred in 2 patients (11.76%).The mean operative time(34.9minutes). Conclusions: Ho:YAG laser lithotripsy is standard in treating ureteric calculi located in the upper, mid and lower ureter. It is able to fragment ureteric stones of all known composition and has an excellent safety profile.